Carrión Disease - Peruvian wart - La Oroya Fever - Rebagliati, Raúl (1935)
Until 1870, endemic in certain localities in the Peruvian Andes intrigued doctors, both Peruvian and foreign. Your ertiología uncertain; its peculiar clinical features, especially red rash, bleeding, tumors consecutively to a incosntante irregular febrile period; their geographical distribution, Limira certain perfectly certain mountain areas; various popular legends concerning its epidemiology; all contributed to the Peruvian Wart considered as mysterious, intangible disease.